SOSIALISASI FITOERAPI PENYAKIT KOLESTEROL DI DESA PETUKANGAN KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Urmatul Waznah; khusna santika Rahmasari; Wulan Agustin Ningrum; Nunung Mufida; Vira Septiya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
One of the diseases commonly found in the community, especially those aged > 40 years, is high cholesterol. This type of disease is a chronic disease that is closely related to people's diet and lifestyle. High cholesterol is also commonly found in children and adolescents with excess body weight. Excessive cholesterol levels can cause plaque that clogs arteries and can cause heart attacks or atherosclerosis which will trigger stroke (Abidi et al., 2006). Non-Communicable Diseases (NCD) is currently one of the health problems of national and global concern, the increase in PTM is closely related to the consumption of foods containing high cholesterol. In order to improve the quality of health, we make efforts to prevent cholesterol. This activity was carried out in collaboration with partners in Petukangan Village, Wiradesa District, Pekalongan Regency. The activities carried out are periodic cholesterol checks and deliver material about cholesterol, namely about the causes of cholesterol, prevention, and cholesterol phytotherapy. Before delivering the material, participants were given a pre-test with an average score of 6.4. After delivering the material, the participants did a post-test with an average score of 9.6. The result of this activity is an increase in public knowledge about cholesterol by 33,3 %. Participants understand more about the causes of cholesterol and can use herbal plants to prevent and treat cholesterol.